Analysis of category level performance on the Praxis® earth and space science: Content knowledge test: Implications for professional learning. Issue 2 (3rd April 2023) - Ndembera, Rachel; Ray, Herman E.; Shah, Lisa; Rushton, Gregory T.
Abstract: A large body of work has shown that science teacher knowledge is one of the most fundamental components of effective teaching and learning. Our study analyzes the Praxis ® Earth and Space Science Content Knowledge Test (ESS CKT) from May 2006 to June 2016. We present one of the largest datasets comprising 11, 273 ESS teacher candidates in order to provide information about their demonstrated ESS CK. Understanding that the benefits associated with teacher retention outweigh the cost of hiring new teachers, our results can be used to design targeted professional learning (PL) experiences for pre- and inservice teachers. Findings from this study are particularly useful while planning inservice topic specific PL for teachers pre- and inservice ESS teachers by answering the following research questions (1) How have examinees performed as a whole in each category on the Praxis ® ESS CKT? (2) Which personal and/or professional characteristics are most associated with examinee performance in each category and how does this inform professional learning? Examinee performance at the category level was analyzed through a five-part process: 1. Confirmatory Factor Analysis: 2. Percent correct; 3. Regression; 4. ANOVA; 5. Scaled points lost. Our findings revealed that examinees demonstrated strongest performance in the topics assessing Earth's Atmosphere & Hydrosphere, Earth Materials & Surface Processes, and Tectonics & Internal Earth Processes and identity History of the Earth and its Life-Forms as topics in need of support. Across categories, we found differences in achievement associated with undergraduate major, gender, and ethnicity. Test-takers with geoscience majors consistently lost fewer points than their out-of-field counterparts, that men outperformed women in the study, and White test-takers lost fewer scaled points than Black and Hispanic candidates. Our recommendations include reviewing our results for alignment with state standards in order to develop comprehensive CK development that will be used as an anchor for focused support on those topics where test-takers tend to demonstrate lowest proficiency.